THE WAVE PRINCIPLE OF THE DISTRIBUTION OF SUBSTANCE IN SOLAR SYSTEM - Smirnov, V. A. (Одеські астрономічні публікації, 2017)
The wave principle of planet system formation and systems of satellites of Jupiter, Saturn and Uranus in the Solar system are considered.